Klik, Beli, Habis? Literasi Keuangan Digital Dalam Mengelola Perilaku Konsumtif Siswa Sekolah Dasar - Miftakh, Eliza Silviana; Nanda, Hanjar Ikrima; Santi, Fitriana (Jayapangus Press, 2024)
The rapid development of digital technology, especially the rise of marketplace platforms, has changed the consumption landscape of society, including children. The ease of access and the variety of product choices offered by marketplaces have made elementary school students increasingly exposed to consumerism culture. This phenomenon raises concerns about the increase in consumer behavior among students who do not yet have a mature understanding of financial management. This study aims to explore the experiences and perceptions of students at SDN X in Malang Regency regarding the use of marketplaces and their influence on consumer behavior. Through a qualitative approach, this study seeks to understand how elementary school students respond to the ease of access and temptation of online shopping offered by marketplace platforms. Data were collected through in-depth interviews with students regarding online shopping activities. The results of the study indicate that the lack of parental control over the use of marketplaces causes students to tend to behave wastefully by buying items that are not related to school needs, spending more money on hobbies, and even being willing to stay up late to participate in flash sales. In addition, the majority of students make transactions with the Cash on Delivery (COD) system without their parents' knowledge, which often causes conflict when the purchased goods arrive. Although students have been introduced to financial literacy in schools, especially in the context of numeracy literacy, digital financial literacy education is still underdeveloped. This finding suggests the need to strengthen the digital financial literacy curriculum to help students manage their finances more wisely and reduce irresponsible consumer behavior. This study is expected to provide insights for educators and parents in supporting the development of more holistic financial literacy among children.